Shaping the future of the fourth industrial revolution a guide to building a better world - Schwab, Klaus 1938-; Davis, Nicholas (Currency, 2018)
Today, technology is changing everything--how we relate to one another, the way we work, how our economies and goverments function, and even what it means to be human. One need not look hard to see how the incredible advances in artificial intelligence, cryptocurrencies, biotechnologies, and the internet of things are transforming society in unprecedented ways. But the Fourth Industrial Revolution is just beginning, says Schwab. And at a time of such tremendous uncertainty and such rapid change, he argues it's our actions as individuals and leaders that will determine the trajectory our future will take. We all have a responsibility--as citizens, businesses, and institutions--to work with the current of progress, not against it, to build a future that is ethical, inclusive, sustainable and prosperous. Drawing on contributions from 200 top experts in fields ranging from machine learning to geoengineering to nanotechnology, to data ethics, Schwab equips readers with the practical tools to leverage the technologies of the future to leave the world better, safer, and more resilient than we found it.